Memorial to the Minister of Health - Loat, Lily (London : National Anti-Vaccination League)
1928-11-30 1928 1920s 8 pages such as those initiated by the Jenner Society and the Imperial Vaccination League, and all have collapsed. To supply public funds for such a purpose would be a public scandal, for the simple reason that (so far as parents at any rate are concerned) more than one half of the community providing those funds is opposed to the practice of vaccination. There might be some justification in these circumstances for anti-vaccinists asking for such a grant-in-aid. But that such a suggestion should be put forward by pro-vaccinists, and above all by pro-vaccinist Medical officials who have already proved their incompetence to formulate a disinterested presentment of the subject, can only be described as a quite unpardonable insult to the public. OUR RECOMMENDATIONS. We respectfully submit that the terrible revelations of the serious risk of post-vaccinal encephalitis partially brought to light by these two reports ought to move Parliament immediately to repeal the Vaccination Acts. If it is considered that that is too hasty a change, we would suggest the adoption of the following recommendations as the absolute minimum required by the present situation:— (1) That the public supply of vaccination should be immediately suspended for at least 10 years on the double ground that (despite the large measure of suspension which has already been effected by the 1907 Conscience Clause) smallpox is now less to be feared than chickenpox, while vaccination has become a disease more dangerous, to young people at any rate, than smallpox itself. (2) That, in future, inquests should be held in every case in which a person dies within two or three months after vaccination or re-vaccination, or, alternatively, that a special note of the association of vaccination with such deaths should be made on the Death Certificate by the Doctor in attendance, and that separate statistical returns should be inserted in regard to these cases in the Registrar-General’s Annual Report; also that in all fatalities from diseases of the brain or nervous system the Death Certificate should give the vaccinal record of the patient. (3) That a Committee, on which, inter alia, acknowledged pro-vaccinists and anti-vaccinists would be equally represented, be appointed, as soon as may be, to investigate the whole subject in the light of the large experience which is now available in regard to the effectiveness of other methods of dealing with and preventing smallpox, which methods have been altogether ignored in the Rolleston Committee’s report. Signed on behalf of the Council of the National Anti-Vaccination League. L. Loat Secretary. November 30th, 1928. 25, Denison House, 296, Vauxhall Bridge Road, London, S.W. I. [Addendum.—Further cases of post-vaccinal encephalitis have occurred in this country in the period of 16 months which have elapsed since the date of the last cases dealt with by the Rolleston Committee. At least 12 fatal cases have been reported in the Press, and doubtless there have been others not so reported. In 1928 38 deaths were reported as occurring within a month of vaccination and on 24 of the death certificates the words "vaccination” or "vaccinia” appeared as a cause of death. It may also be stated that in the Netherlands 139 cases of post-vaccinal encephalitis were reported during 1923 to 1927, of which 41 died, and that as a consequence of these cases the compulsory enforcement of vaccination has been temporarily suspended.] Printed by Vacher & Sons, Ltd., Westminster House, S.W.l (61767), and published by the National Anti-Vaccination League, 25, Denison House, 296, Vauxhall Bridge Road, London, S.W.l. 292/840/1/13